Tafsir, Ta'wil, dan Hermeneutika Suatu Paradigma Baru dalam Pemahaman Al-Qur'an - Shihab, Muhammad Quraish (SUHUF, 2009)
Studies on interpretation, exegesis, and hermeneutics are very wide for the difference of the scope of definition presented. Interpretation and exegesis are used to understand the words, sentences and the God's messages. Many Muslim scholars considers both have the same meaning, whereas for hermeneutics means the explanation about the meaning of the God's messages. Therefore, if hermeneutics is under-stood as the above explanation, it is not wrong that actually, herme-neutics has long been known by the Muslim scholars before the emergence of Western hermeneutics. As to other method of the inter-pretation of the Qur'an, Islam does not ban hermeneutics to doubt the Qur'an as long as that process drives the doer to positively think about the Qur'an and not to make the doer in pessimistic doubtful, pessimistic doubtful accompanied by bad assumption toward the Qur'an. Although some Muslim scholars allow the use of hermeneu-tical study in understanding the Qur'an, however, there are some tight requirements in using it. One of them is if there is certain indication (qaranah) which makes it hard to understand the external meaning